Prestasi Kincir Air Sudu Melengkung Tipe Undershot Sebagai Pembangkit Listrik Tenaga Air Pikohidro Pada Saluran Irigasi - Sugiman Sugiman; Asral Asral; Feblil Huda (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The study waterwheel performance has done by utilizing the potentional of water energy source which is found inirrigation channel in Koto Tibun Village, Kampar Subdistrict, Kampar Regency. The purpose of this study is todetermine the achievement of the waterwheel curved undershot type on the irrigation canal. The design has beendone to get a curved angle of 54.21⁰ with a blade length of 0.7 m. The result is obtained from the test is the massof water type (ρ) 972 Kg / m³, the maximum water wheel eaya 244.3736 W at the 5th discharge (Q5) is 0.2221 m³/ s, and the highest efficiency 58.62576% at the discharge 3 (Q3 = 0.1671 m³ / s) with 1.3 rpm and 186.874 W.Achievement of waterwheels curved undershot curve can be seen through the power graph and the efficiency ofthe rotation indicating that the greater the value it will be along with the increase in rotational speed and willdrop at a certain speed of play.Keywords: waterwheel, undershot, curved blade, irrigation, picohydro